1979
DOI: 10.1097/00006842-197902000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Renin, Cortisol, and Aldosterone During Transcendental Meditation

Abstract: The effects of transcendental meditation (TM) on plasma renin activity (PRA) and plasma concentrations of aldosterone, cortisol, and lactate were studied by measuring these variables before, during, and after 20--30 min of meditation. Subjects, who rested quietly rather than meditating, served as controls. There were no differences in the basal values for these variables between meditators and controls, but controls, in contrast to meditators, showed a significant increase in cortisol between the first (A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Green and Green (1987) found no decreases in cortisol across a brief 20-minute relaxation or visualization session, although they did not utilize a control group. Likewise, in a study of cortisol outcomes across a meditation intervention, Michaels et al (1979) noted an initial increase in cortisol in a rest-only control group. In light of these findings, it is possible that group sizes, characteristics of control conditions, and the short-term nature of the intervention may have disguised cortisol effects that have been shown in longer term stress-reduction interventions (Bernstein et al, 2000;Grossman et al, 2004;Matousek et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Green and Green (1987) found no decreases in cortisol across a brief 20-minute relaxation or visualization session, although they did not utilize a control group. Likewise, in a study of cortisol outcomes across a meditation intervention, Michaels et al (1979) noted an initial increase in cortisol in a rest-only control group. In light of these findings, it is possible that group sizes, characteristics of control conditions, and the short-term nature of the intervention may have disguised cortisol effects that have been shown in longer term stress-reduction interventions (Bernstein et al, 2000;Grossman et al, 2004;Matousek et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…A reduction in both glucocorticoids and oxidative stress has been documented in people who practice meditation regularly. Hormonal reactions to stressors, in particular plasma cortisol levels, are lower in people who meditate than in people who do not [31–36], suggesting that it is possible to modulate the neuroendocrine system through neurological pathways. Analysis of oxidative stress levels in people who meditate indicated that transcendental meditation, Zen meditation and Yoga correlate with lower oxidative stress levels [3743].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] "On Transcendental Meditation, the cortisol levels was a significant drop in the yoga group, mainly due to decrease release of stress hormone "cortisol" from adrenal cortex. [18][19][20][21][22] The practice of "asanas" relaxes the muscles and joints which influences the hemodynamic mechanism, thereby improving blood circulation to vital organs. This may also activate the neuro-endocrine axis which is important in facing physical and mental stress.…”
Section: Discussionmentioning
confidence: 99%